2002
DOI: 10.1177/002215540205001014
|View full text |Cite
|
Sign up to set email alerts
|

HPV DNA Detection by In Situ Hybridization with Catalyzed Signal Amplification on Thin-layer Cervical Smears

Abstract: S U M M A R YThin layer-based technology in cervical cancer screening now allows both Papanicolaou staining and HPV testing on the same sample. Here, we show that in situ hybridization with catalyzed reporter deposition is a powerful HPV detection method when applied on thin-layer cervical smears, allowing distinction between two staining patterns suggestive of two different physical states of HPV DNA, where diffuse signals are suggestive of episomes and punctate signals are suggestive of viral DNA integration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…A diffuse hybridization pattern was not observed. Others have shown that the punctate pattern of hybridization correlates with viral DNA integration, whereas a diffuse signal correlates with episomal HPV (31). The hybridization signals were strictly limited to the carcinoma and the associated dysplastic epithelium.…”
Section: Resultsmentioning
confidence: 88%
“…A diffuse hybridization pattern was not observed. Others have shown that the punctate pattern of hybridization correlates with viral DNA integration, whereas a diffuse signal correlates with episomal HPV (31). The hybridization signals were strictly limited to the carcinoma and the associated dysplastic epithelium.…”
Section: Resultsmentioning
confidence: 88%
“…This method allowed us to detect as few as one or two copies of HPV DNA as previously described [9]. The physical state of the virus (integrated, episomal, or mixed) had been determined by the pattern of the ISH signal, a dotted pattern corresponding to the integrated form of the virus, a diffuse pattern to its episomal form [9,11,12].…”
Section: Hpv Detection By Ishmentioning
confidence: 99%
“…In situ hybridization was performed by using cold probes (Enzo Diagnostic, New York, NY) revealing the 6/11, 16/18, and 31/33/51 HPV genomes according to a procedure previously described [9]. Briefly, the slides were deparaffinized with toluene, rehydrated with absolute alcohol, and finally rinsed with water.…”
Section: Hpv Detection By Ishmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent adaptation of the method to slide-based applications has demonstrated remarkable gains in sensitivity for FISH for detection of protein (Davies et al 1999), DNA (Acar et al 2002;McKay et al 1997;Schriml et al 1999), and RNA targets (Breininger and Baskin 2000;Qian et al 2001;Tata 2001;van de Corput et al 1998a, b;van Gijlswijk et al 2000;Wagner et al 1998;Yang et al 1999;Zaidi et al 2000;Zhang and Kitching 2000), and for bright field molecular applications (Zehbe et al 1997;Tubbs et al 2002a, b;Speel et al 1998;Samama et al 2002;Wiedorn et al 1999;Plummer et al 1998;Sano et al 1998). In the present study we combined the two approaches for simultaneous and robust immunophenotypic segregation of populations for genotyping using multicolored FISH probes.…”
Section: Introductionmentioning
confidence: 99%